PRESIDENTIAL RE-ELECTION IN LATIN AMERICA: CURRENT TRENDS - A. . Rylova (Ибероамериканские тетради, 2016)
The early 21st century saw a “boom” of presidential re-elections in Latin America. After almost a universal ban on re-election in the late 1980s - early 1990s, increasingly more countries amend their constitutions to authorize re-election of the head of state. The present article analyzes existing models of re-election of presidents in Latin America, examines the latest trends and changes in constitutions.